ANALISIS PENGELOLAAN KEUANGAN KELOMPOK TANI UNTUK MENINGKATKAN KESEJAHTERAAN PETANI PORANG - Putri, Vivi Harmika; Isharijadi, Isharijadi; Yusdita, Elana Era (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
Abstract : This study aims to determine the financial management of farmer groups to improve the welfare of porang farmers. The porang plant is one of the export commodities from villages in Indonesia but is not well known to many people. This study used a descriptive qualitative method with interviews which showed that the capital used by the farmer groups apart from cash, also provided assistance from outside parties. For porang land management, there is a special land for farmer groups which is generally managed with a mutual cooperation system, while for individual land management it depends on each person. The income of the farmer group will be divided evenly after the income from the sale is taken from the initial capital. Kata Kunci/Keywords: Financial Management; Farmer Groups; Porang Plants